Pengaruh Latihan Lari Kontinyu Dan Circuit Training Terhadap Peningkatan VO₂Max Pemain Futsal - Masdar, Rifka Irvandy; , Wahyuni,S.Fis.,M.Kes (2017)
VO2max very influential in our daily lives, so as to increase physical activity, especially futsal players in order to achieve maximum performance. In an effort to increase VO2max exercise should out carefully, systematically and regulary. This study aims to determine the increase VO2max futsal players through continuous traning and cicuit training. To determine the effect of continuous training and cicuit training to increase VO2max futsal players. This type of research is an experimental research design with Pre and Post Test Two Group Design. The population in this study is Tambusai FC futsal players who totaled of 10 people. Normal distribution of data and homogeneous variance., hypotesis testing on a continuous training using paired sample T-Test with tvalue of -4.081, Sig (p value) 0,015 smaller than 0.05 (0.015 <0.05) means there VO2max increased influence of futsal players. And the circuit training tvalue of 8.237, with Sig (p value) of 0,001 is smaller than 0.05 (0.001 <0.05) means that there is the influence of an increase in VO2max. To test the effect of different uses Independent Sample T-Test with tvalue of -4.081, with Sig (p value) 0.004 smaller than the level value of 0.05 (0.004 <0.05) means that difference in the effect of circuit traing to increase VO2max futsal players. Continuous training and cicuit training can improve VO2max futsal players. But the provision of circuit training is more effective in improving VO2max than continuous training.